2020
DOI: 10.1111/jfpe.13511
|View full text |Cite
|
Sign up to set email alerts
|

Microwave pre‐treatment for vacuum drying of orange slices: Drying characteristics, rehydration capacity and quality properties

Abstract: Microwave pre‐treatment for vacuum drying is a promising method in order to enhance heat and mass transfer rate. In this study, the influences of microwave pre‐treatment (90 W 30 min) on vacuum drying conducted at different combinations of drying temperature and absolute pressure (60, 70, and 80°C with 15 and 30 kPa) were investigated by evaluating the drying characteristics, rehydration capacity, and some quality attributes of orange slices. The vacuum drying treatments were carried out both with (MWVD) and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 79 publications
(84 reference statements)
3
13
0
Order By: Relevance
“…Bozkir [13] dehydrated the Valencia variety with the convective drying method at 50 °C, 60 °C, and 70 °C and emphasized that the color change (ΔE) decreased due to the increase in temperature. We noticed that the color parameters of fresh orange slices measured in a study conducted by Karabacak et al [58] were in parallel with our results. Deng et al [2] dehydrated the orange peels with five ambient temperatures between 50-70 °C and, unlike our finding in our study, found that the most color loss occurred at 65 °C.…”
Section: Color Parameters Browning and Whitening Indexsupporting
confidence: 91%
See 1 more Smart Citation
“…Bozkir [13] dehydrated the Valencia variety with the convective drying method at 50 °C, 60 °C, and 70 °C and emphasized that the color change (ΔE) decreased due to the increase in temperature. We noticed that the color parameters of fresh orange slices measured in a study conducted by Karabacak et al [58] were in parallel with our results. Deng et al [2] dehydrated the orange peels with five ambient temperatures between 50-70 °C and, unlike our finding in our study, found that the most color loss occurred at 65 °C.…”
Section: Color Parameters Browning and Whitening Indexsupporting
confidence: 91%
“…Bozkir [ 13 ] analyzed the vitamin C content of orange slices dried at 50, 60, and 70 °C along with fresh ones and determined that slices dried at 50 °C and 70 °C had 56% and 79% less vitamin C concentrations, respectively, than fresh ones. Karabacak et al [ 58 ] found that the ascorbic acid content of orange slices dried by vacuum drying was approximately 2–2.5 times reduced compared to fresh ones. Deng et al [ 2 ] measured the vitamin C content of convective dried orange peels at different temperatures from 50 to 70 °C.…”
Section: Resultsmentioning
confidence: 99%
“…As a novel drying method, microwave (MW) drying converts electromagnetic energy into heat energy to heat materials volumetrically [ 14 ]. Due to its fast drying rate and being easy to operate, it has been widely used in drying and processing of cereals, fruits, vegetables and aquatic products [ 15 , 16 ]. Kipcak and İsmail [ 17 ] studied the effects of MW drying power on the drying kinetics of fish and observed that drying time decreased as MW power increased, and the MW power level was the main factor affecting the color change in the treated material.…”
Section: Introductionmentioning
confidence: 99%
“…The D eff amounts recorded in this study for tiger nut is within the broad range of 10 −8 –10 −12 m 2 s −1 to dry food materials [ 24 ]. D eff recorded in this study is relatively higher than hot-air drying of dika kernels and nuts [ 23 ] but lower than ultrasonic hot-air drying of walnuts [ 25 ].…”
Section: Resultsmentioning
confidence: 80%
“…At this stage, the sample's moisture diffuses rapidly through the pieces' pores; thus, there is a high loss factor at higher moisture content. This movement increases the water vapour pressure inside the pores and results in pressure-inducing pore openings in the tiger nut's tissues [ 23 ]. The D eff amounts recorded in this study for tiger nut is within the broad range of 10 −8 –10 −12 m 2 s −1 to dry food materials [ 24 ].…”
Section: Resultsmentioning
confidence: 99%